The Physical Fitness In Volleyball Club at SMAN 4 Of Central Bengkulu - Deni Kusuma Saputra; Mariska Febrianti; Tito Parta Wibowo (Perkumpulan Dosen Muda Bengkulu, 2020)
This research was conducted with the aim of knowing the physical fitness in Volleyball Club at SMA N 4 of Central Bengkulu. The design of this research is descriptive quantitative research. The method used in this research is a survey method with data collection techniques using TKJI test. The population of this study were students at SMA N 4 of Central Bengkulu with a total sample of 30 people consisting of 20 male students and 10 female students using total sampling technique. The variables in this study were students at SMA N 4 of Central Bengkulu. The data were collected using the physical fitness test for the 16-19 year category (Depdiknas, 2010: 3), and the data analysis technique used was descriptive statistical techniques with frequency and percentage through categorization. Based on the results of research and data analysis obtained from the physical fitness test in Volleyball Club at SMA N 4 of Central Bengkulu, there were 3 people or 10% were categorized as good, 21 people or 70% were categorized as moderate and 6 people or 20% were categorized as lacking. Based on the results of this study, it can be concluded that the physical fitness of volleyball club at SMA N 4 of Central Bengkulu is in the moderate category.